Pembelajaran Daring Berbasis Pendekatan Studi Kasus di Era Digital - Syakur Wildan; Husni Idris (AS-SABIQUN, 2023)
Today's digital age learning is not teacher-centered, it will be entirely student-centered. This is because all aspects of learning use a lot of supporting media such as learning videos, PowerPoint, and so on. Planning needs to be done in terms of the readiness of teachers and students to utilize information and communication technology, such as the internet from laptops and computers as well as applications via smartphones. The case study approach as an approach to online learning is an alternative way to provide ways to make learning more innovative and fun. In essence, the case study in question is seeking data information aimed at solving a particular problem or case in an attempt to provide a precise and accurate solution by considering the data obtained from the field. Therefore, the case study approach in online learning is expected to be a new breakthrough in distance learning which has limitations in monitoring students intensely because they can only see their body movements. The research method used is a qualitative research method with observation and interview techniques which are the main data collected during the research. Data analysis used by researchers is data reduction, data presentation, and verification. This study aims to provide insight into the educational component in managing ways in the digital era by using targeted technology. Apart from that, educators and students must be able to adapt to today's more digitalized environment.